Building purchase interest through Instagram content: analysis of @Mrocoffee account - Prasetya, Wibawa; Bathesta, Yovi; Zahar, Hicksan; Harwinda, Alfilonia (Penerbit Universiti Kebangsaan Malaysia, 2024)
With the increasing use of social media, businesses will leverage platforms such as Instagram to showcase their products to attract potential customers. It is important for businesses to understand how to create content on these platforms to influence consumer behavior. Although social media is widely used for marketing purposes, the specific impact of content on purchasing interest and decision-making remains relatively underexplored, especially in the context of business Instagram accounts like @Mrocoffee. This study aims to explore the relationship between content posted on the Instagram account @Mrocoffee and purchasing interest and decision-making among its followers/customers. The research methodology used is a quantitative survey with subjects being followers/customers aged 17 who are customers and followers of Instagram @Mrocoffee. Sampling was conducted using purposive sampling from an unknown population size. A sample size of 68 was determined using the Lemeshow formula. The quantitative survey will measure variables related to Instagram content @Mrocoffee, purchasing interest, and decision-making. Data processing will use Smart PLS. The results indicate that visual appeal, storytelling, and interaction with followers through interactive content significantly influence purchasing interest and decision-making @Mrocoffee. Additionally, update frequency and message consistency also play a crucial role in maintaining customer interest and loyalty. Practical Recommendations: @Mrocoffee can leverage user-generated content and collaborate with influencers to enhance brand visibility and credibility. Academic Recommendations: Further research is needed to delve deeper into the aspects of content strategy on Instagram and its impact on consumer behavior across various industries.